Implementasi Solidaritas Sosial Emile Durkheim Bagi Pasangan Suami Istri: Suatu Bentuk Perwujudan Keharmonisan Keluarga: Implementation of Social Solidarity for Married Couples: A Form of Manifestation of Family Harmony - Marwah, Marwah; Nur Khotimah, Adiva; Isnaini, Lailatul (ISTIDLAL, 2023)
Seeing husband and wife disputes that lead to divorce caused by a lack of belonging and respect for each other, this study aims to describe the form and efforts of husband and wife solidarity in realizing harmony with them. The method used in this research is a literature study with a sociological normative approach. Next this research will be analyzed using Emile Durkheim's theory of solidarity. The results showed that family harmony can be obtained through the closeness and openness of husband and wife. Closeness and openness here according to Emile Durkheim in the theory of social solidarity is obtained through mutual assistance and cooperation. Furthermore, this study shows the realization of harmony through mechanical solidarity where each married couple has a sense of mutual awareness or mutual help in achieving common goals. Then the forms of business in realizing family harmony that can be done by husband and wife through mutual assistance and cooperation are Doing housework together, mutual openness in managing family finances, being open to each other in communicating and understanding each other's roles